Salmonella Typhi: a rare cause of parotid abscess - Anandan, Yamini (BMJ Case Rep, 2020)
The incidence of extraintestinal infection caused by Salmonella spp has been increased during the past decade. Here we report a case of a parotid abscess caused by Salmonella enterica subspecies enterica serotype Typhi (S. Typhi) in an individual without any significant abnormality of the parotid gland. A 68-year-old man presented to the surgical department with high-grade intermittent fever associated with painful swelling over the right side of the face, extending into the neck. An ultrasound of the neck revealed an abscess of the right parotid gland. S. Typhi was isolated from the pus drained from the parotid gland. The patient was treated with intravenous followed by oral cephalosporin for a period of 7 days. This case gives an insight into one of the rarer aetiological agents causing parotid abscess.